2017
DOI: 10.1051/matecconf/201710608047
|View full text |Cite
|
Sign up to set email alerts
|

Planning the amount of construction work by modelling the industry competitive field

Abstract: Abstract.The article gives the author's interpretation of concepts such as the model of competitive field and competitive market conditions in the field, and shows how to quantify the competitive field provided adequate statistical base for the operation of enterprises in market competition. The authors offer a competitively construction company with a model of the competitive field, which gives the following definition: a model of a competitive field is a graph crossing function of the life cycle of concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…He suggested that in an exacerbation of the situation, to give lower-ranking officers participating in the battle the freedom to make decisions and direct actions. In addition, Clausewitz recommended the creation of smaller maneuverable units and stressed the importance of dispelling the "fog of war" through intelligence [7,8,9]. His ideas are still used by modern armed forces.…”
Section: Resultsmentioning
confidence: 99%
“…He suggested that in an exacerbation of the situation, to give lower-ranking officers participating in the battle the freedom to make decisions and direct actions. In addition, Clausewitz recommended the creation of smaller maneuverable units and stressed the importance of dispelling the "fog of war" through intelligence [7,8,9]. His ideas are still used by modern armed forces.…”
Section: Resultsmentioning
confidence: 99%
“…The entire amount of money is expressed by an indicator, which we will designate as a monetary base [11]. Accordingly, the monetary base is the sum total of all funds.…”
Section: Resultsmentioning
confidence: 99%
“…So, the development of programs is connected with the strengthening of centralization in decision-making processes in certain areas of sectoral planning [6,7]. The programs are developed to solve those problems that can not be solved at the moment effectively on the basis of the existing (sectoral and territorial) division of functions in the organizational structure of the planning system and the methods adopted for coordinating planning decisions.…”
Section: Discussionmentioning
confidence: 99%